Design and Optimization of a Novel Compliant Z-Positioner for the Nanoindentation Testing Device - Minh Phung Dang; Thanh Dat Le; Hieu Giang Le; Chi Thien Tran (Machines)
Compliant mechanisms are extensively utilized in precise positioning systems. This work presents a novel compliant fine Z-positioner for directing the indenter in a nanoindentation testing positioning system. Initially, the suggested positioner consists of a novel hybrid symmetric compliant displacement amplifier of four-lever and Scott Russell structures combined with a parallel guiding mechanism. Subsequently, a static–dynamic characteristic of the proposed positioner is modeled by the pseudo-rigid body method and the Lagrange technique. Based on the FEA results, the parasitic motion error of the developed fine Z-positioner was 0.0956%. Thirdly, the analytical result was verified by FEA analysis, and the error between the two methods was 0.5869%. Therefore, the proposed analytical approach was reliable for quickly assessing the output response of the proposed positioner. Finally, to enhance the quality of the proposed structure’s response, the main design variables of the fine Z-positioner are optimized using the Firefly algorithm. The optimal findings indicated that the first natural frequency occurs at around 220.16 Hz. The imprecision between the optimal result and the FEA result was 9.67%. The analytical results are in close agreement with the confirmed FEA result. The prototype was manufactured by the computerized numerical milling method. The inexactness between the FEA outcome and the experimentation outcome was 11.04%. Based on the FEA and experiment results, displacement amplification proportions were 6.8725 and 8, respectively. In addition, the experimental results demonstrated a good linear relationship for guiding mechanisms in nanoindentation testing positioning systems.